2022
DOI: 10.3390/en15186621
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic Analysis of Hybrid Renewable Energy Systems Designed for Electric Vehicle Charging: A Case Study from the United Arab Emirates

Abstract: The United Arab Emirates is moving towards the use of renewable energy for many reasons, including the country’s high energy consumption, unstable oil prices, and increasing carbon dioxide emissions. The usage of electric vehicles can improve public health and reduce emissions that contribute to climate change. Thus, the usage of renewable energy resources to meet the demands of electric vehicles is the major challenge influencing the development of an optimal smart system that can satisfy energy requirements,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…It is ascertained that the optimal system could generate annual surplus electricity of 22,006 kWh with a COE of about $0.06743/kWh. The analysis in [54] also reveals the environmental benefit of the proposed model. Muna and Kuo [55] investigate the techno-economic and environmental analysis of EVCSs using hybrid energy systems with various storage device technologies in three different locations in Ethiopia.…”
Section: A Literature Reviewmentioning
confidence: 88%
See 1 more Smart Citation
“…It is ascertained that the optimal system could generate annual surplus electricity of 22,006 kWh with a COE of about $0.06743/kWh. The analysis in [54] also reveals the environmental benefit of the proposed model. Muna and Kuo [55] investigate the techno-economic and environmental analysis of EVCSs using hybrid energy systems with various storage device technologies in three different locations in Ethiopia.…”
Section: A Literature Reviewmentioning
confidence: 88%
“…Their results indicate that an electric CS is only viable when the acquisition cost is maintained at the lowest to return 1.47 times the initial investment with regard to the life-cycle cost. The study in [54] assesses different systems of REbased HES for EV charging in the capital city of the UAE.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…These publications involve authors from a variety of countries, the most prominent nationalities being China (38), India (20), Canada (12), the UK (12), Saudi Arabia (11), Iran (10), South Korea (10), the USA (10), Spain (9), and Japan (7). Additionally, when considering the number of citations received by articles originating from different countries, the leading nations are as follows: USA (423), China (127), South Korea (71), Romania (66), Turkey (36), India (29), South Africa (25), the United Kingdom (18), Qatar (14), and Bulgaria (6).…”
Section: Energy Generationmentioning
confidence: 99%
“…This encompasses a spectrum of measures that have been adopted in the UAE, including but not limited to fiscal incentives, financial subsidies, regulatory standards, and infrastructural investments (Benny, 2023) [4]. AlHammadi et al ( 2021) [17] demonstrated that the implementation of technological solutions incorporating efficient EV charging stations leads to a reduction in the cost associated with charging a vehicle. The UAE's deployment of state-of-the-art charging infrastructure seamlessly integrates advanced technologies and operational efficiencies as strategies to enhance the economic feasibility and convenience of EV adoption.…”
Section: Economic Incentives Associated With Ev Adoptionmentioning
confidence: 99%